Controllable formation of MoS2 via preferred crystallographic orientation modulation of DC-sputtered Mo thin film - Chelvanathan P.; Shahahmadi S.A.; Ferdaous M.T.; Sapeli M.M.I.; Sopian K.; Amin N. (Elsevier B.V., 2023)
Layered semiconductors; Molybdenum compounds; Molybdenum plating; Sputtering; Controllable formation; Crystallographic orientations; Czts solar cells; Mo films; MoS2; Packing factor; Sulphurization; Vacuum thermal annealing; Thin films